An Investigation of the Impact of Cylindrical Grinding Parameters on Surface Roughness - Kasim, Mohd Shahir; Salleh, Mohd Rizal; Abd Rahman, Ammar; Abd Rahim, Nurul Hidayah (2008)
This paper presented an investigation of impact of cylindrical grinding parameter to surface roughness on SUS316 stainless steel. Grinding is the most common process when the workpiece demands good surface, dimensional and geometrical quality. In this experiment, the finding is the actual effect of surface roughness and the relationship for each parameter that have been choosing. The method that has been used to design the experiment was Design of Experiment (DOE) full factorial with two levels. The surface roughness of the workpiece has been analyzed by using a Portable Roughness Measurement Machine. The data will be compared and analyzed using MINITAB 14 software. The graphs have been created to shows the optimum factor and interaction between the factors. This experiment runs using three factors which are traverse speed, work speed and depth of cut.